2020
DOI: 10.3389/fonc.2020.00033
|View full text |Cite
|
Sign up to set email alerts
|

PLXNC1 Enhances Carcinogenesis Through Transcriptional Activation of IL6ST in Gastric Cancer

Abstract: Background: Transcriptional factors (TFs) are responsible for orchestrating gene transcription during cancer progression. However, their roles in gastric cancer (GC) remain unclear.Methods: We analyzed the differential expressions of TFs and, using GC cells and tissues, investigated plexin C1 (PLXNC1) RNA levels, as well as PLXNC1's clinical relevance and functional mechanisms. The molecular function of PLXNC1 was evaluated in vitro and in vivo. Kaplan-Meier curves and the log-rank test were used to analyze ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Further, as NFkB is suggested to drive TAMs towards a more anti-inflammatory environment, it is plausible that this subpopulation plays a role in the observed peripheral cells' evolution towards an anti-inflammatory environment. Furthermore the enrichment of other transcription factors from the same cluster (BATF, PLXNC1, MTF1) as NFkB have been shown to upregulate in other cancers [72][73][74] suggesting NFkB to exert and a pro-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as NFkB is suggested to drive TAMs towards a more anti-inflammatory environment, it is plausible that this subpopulation plays a role in the observed peripheral cells' evolution towards an anti-inflammatory environment. Furthermore the enrichment of other transcription factors from the same cluster (BATF, PLXNC1, MTF1) as NFkB have been shown to upregulate in other cancers [72][73][74] suggesting NFkB to exert and a pro-tumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is involved in local tissue remodeling and immune cell infiltration ( Feigerlovã and Battaglia-Hsu, 2017 ). The IL-6/STAT3 signaling pathway has been investigated in gastric cancer research, and activation of IL6ST enhances carcinogenesis ( Chen et al, 2020 ). Although it has been previously reported that IL-6 stimulates STAT3 phosphorylation in acute kidney injury, the mechanism of IL-6 in the STAT3/NF-kB signaling pathway remains to be investigated ( Ranganathan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of certain genes altered following treatment of JQ1 and SAHA, indicating that these drugs might inhibit tumor growth by regulating the expression of some key genes. PLXNC1 is reported as an oncogene in liver carcinoma (Odabas et al, 2018) and gastric cancer (Chen et al, 2020) and also played a part in TC progression. MiR-4500 repressed PTC development by decreasing PLXNC1 expression (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%